2021
DOI: 10.3389/fmed.2021.624924
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Benefit of Convalescent Plasma in COVID-19: A Systematic Review and Meta-Analysis

Abstract: Importance/Background: With a scarcity of high-grade evidence for COVID-19 treatment, researchers and health care providers across the world have resorted to classical and historical interventions. Immunotherapy with convalescent plasma (CPT) is one such therapeutic option.Methods: A systematized search was conducted for articles published between December 2019 and 18th January 2021 focusing on convalescent plasma efficacy and safety in COVID-19. The primary outcomes were defined as mortality benefit in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 66 publications
(66 reference statements)
2
45
2
1
Order By: Relevance
“…Similarly, the study conducted by Janiaud et al ( 40 ) involving a total of 11,782 patients from 10 RCTs indicated that CP was not associated with a decrease in all-cause mortality or any benefit for other clinical outcomes. The other two meta-analysis showed a reduction in mortality but disappeared in RCTs, strengthening our results ( 41 , 42 ). Contrary to our study, several previous meta-analyses ( 43 46 ) showed that CP could help reduce mortality in COVID-19 patients, and their level of evidence was lower than the present study because most of them included not only RCTs but also observation studies in their analysis.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the study conducted by Janiaud et al ( 40 ) involving a total of 11,782 patients from 10 RCTs indicated that CP was not associated with a decrease in all-cause mortality or any benefit for other clinical outcomes. The other two meta-analysis showed a reduction in mortality but disappeared in RCTs, strengthening our results ( 41 , 42 ). Contrary to our study, several previous meta-analyses ( 43 46 ) showed that CP could help reduce mortality in COVID-19 patients, and their level of evidence was lower than the present study because most of them included not only RCTs but also observation studies in their analysis.…”
Section: Discussionsupporting
confidence: 86%
“…The initial results were very promising, but the intervention group not only included COVID-19 patients, but also those with SARS, MERS, and influenza ( Aviani et al, 2021 ). In a meta-analysis of COVID-19 patients, Bansal et al, showed that adding convalescent plasma to the standard of care reduced mortality among patients ( Bansal et al, 2021a ). A second meta-analysis by Janiaud et al, did not demonstrate the beneficial effect of administering convalescent plasma to patients ( Janiaud et al, 2021 ).…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 99%
“…Most recently, the US Food and Drug Administration (FDA) granted Emergency Use Authorization for two neutralizing antibody cocktails (casirivimab/imdevimab and bamlanivimab/etesevimab), as well as monotherapy with bamlanivimab for treatment of ambulatory patients who have a high risk of progressing to severe disease [6]. On the other hand, individual randomized control trials on the efficacy of convalescent plasma (CP) have shown negative results [7][8][9][10][11][12][13][14][15][16][17]; however, two recent meta-analyses have demonstrated the efficacy of convalescent plasma (CP) in mortality reduction of patients with severe COVID-19, similarly to the results of several matchedcontrol trials [18,19]. A survival benefit of patients treated with CP was recently shown by our group in a matched propensity score analysis of 59 patients [20].…”
Section: Introductionmentioning
confidence: 99%